Trash Tiddas:Blak queers, terrible TV and the Blachelorette - Day, Madi; DeVries, Tully; LF, Amy; Scobie, Brooke (AlterNative: An International Journal of Indigenous Peoples, 2024)
Trash Tiddas is a podcast about Blak—a reclaiming of Black from English as a colonising language, and used by Aboriginal and Torres Strait Islander people—Millennial life and culture produced by First Nations digital content platform Awesome Black. In this article, the hosts Tully DeVries, Amy LF and Brooke Scobie speak with Madi Day about the cultural significance of Brooke Blurton’s season as Australia’s first Blachelorette—Blak, queer Bachelorette. The authors discuss Aboriginal and Torres Strait Islander presence and absence in Australian reality TV, and the rigid behavioural standards imposed on Blak participants on reality TV dating shows. In doing so, we identify a pattern of refusal of colonial norms in alternative Blak millennial content and how humour is used by Blak women and queer millennials in the face of White propriety and colonial impositions on Blak love and lives.